2021
DOI: 10.3389/fmed.2021.771352
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Annual Economic Burden of Dry Eye Disease Based on a Multi-Center Analysis in China: A Retrospective Study

Abstract: Purpose: To conduct a multi-center analysis and assess the economic burden due to dry eye disease (DED) in China.Design: A retrospective and cross-sectional study.Methods: Patients (n = 598) with diagnosed DED were recruited from 3 eye centers (in central, southeast, and northeast China) from 1 January 2018 to 31 December 2018. Data were collected regarding the examination, pharmacological therapy, and non-pharmacological therapy fees. Sub-group analyses were stratified by eye center, DED severity, types of DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…[ 7 ] The primary mechanism leading to DED is hyperosmolarity of the tear film and inflammation of the ocular surface. [ 8 ] The tear film of the eye consists of aqueous, mucous, and lipid components. Instability of one or more of these components can cause tear film breakdown, resulting in symptoms of DED.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] The primary mechanism leading to DED is hyperosmolarity of the tear film and inflammation of the ocular surface. [ 8 ] The tear film of the eye consists of aqueous, mucous, and lipid components. Instability of one or more of these components can cause tear film breakdown, resulting in symptoms of DED.…”
Section: Introductionmentioning
confidence: 99%
“…DED is potentially associated with ocular surface injury and visual disturbance, which makes it the most common diagnosis in the eye care service [ 5 ]. Additionally, DED adversely affects the quality of life and decreases the workforce productivity, placing a large financial burden on patients and medical care system [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, there is a huge economic burden on the health care system. A 2018 multicenter study in China showed annual DED administration costs of approximately $10.42-$166.6 billion [6]. Currently, the treatment of DED consists of moistening the ocular surface, promoting repair, anti-inflammatory, antioxidant, surgical, and physical therapy.…”
Section: Introductionmentioning
confidence: 99%